Modern weapons and military equipment for issue 2-2022 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Russian army receives first modernized 203mm 2S7M Malka self-propelled howitzers, Can NATO’s Javelin Missile Wipeout Russia’s Tanks? Russia’s Predator-Like Drone Is Now Shooting Down Other Drones, Radar developers adapt for tracking hypersonic threats.